Legiony włoskie i żołnierze - obywatele w literaturze czeskiej = Italian legions and citizen soldiers in Czech literature - Rell, Tomáš (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the phenomenon of Czech legionary literature as an integral part of the cultural heritage of the First Republic. It specifically focuses on the lesser-known Italian front. It brings to light the forgotten legionnaires and militiamen who entered based on personal experience in the literary field and contributed to the development of Czech legionary literature. The mentioned model examples are the writer and teacher František Horečka; poet novelist playwright translator and promoter of Italian realities Bartoš Vlček; and writer and librarian Václav Fryček.
Keywords: literatura legionowa frontu włoskiego z I wojny światowej; Horečka, František (1894-1976); Vlček, Bartoš (1897-1926); Fryček, Václav (1897-1969); First World War Italian front legionary literature